(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The main aim of the article is to give the reader a range of lively, spoken Russian proverbs and sayings. The article is based on recordings made mainly in the 1930s and, partly, earlier. Our contemporary proverbial repertoire includes a huge number of original Russian proverbs. This age-old stock of folk wisdom does not remain unchanged. In the process of the growth and development of social relations and the abolition of remnants of capitalism in the minds of people some proverbs are forgotten and others are created.Russian proverbs and sayings, growth and development of social relations, stock of folk, sharp words, socio-historical experience.